THE EFFECT OF INTERNAL LOCUS OF CONTROL AND BURNOUT CONDITION ON EMPLOYEE PERFORMANCE OF PT BIO FARMA (PERSERO) BANDUNG - Suherman, Usep Deden; Gliserlda, Alda (Indonesian Journal of Strategic Management, 2025)
The purpose of this research is to ascertain whether internal locus of control influences something partially and simultaneously and burnout condition on performance at PT Biofarma (Persero) Bandung. Verifiable descriptive study using a quantitative approach is the methodology employed. Using random sampling techniques, the purposive sampling technique is used in the sample process. The primary and secondary data used were gathered directly from relevant sources and from PT. Biofarma (Persero) Bandung's official website and data collection techniques using questionnaires. The study's findings demonstrated that the Locus of Internal Control significantly and partially affected performance. The performance was not significantly affected by the burnout condition, nor did it have any influence. Employee performance is significantly impacted by both the burnout condition and the locus of internal control at the same time.